Analisis Structural Equation Modeling Manajemen Kepemimpinan, Motivasi Dan Disiplin Kerja Karyawan Kampus Islam - Ziaulhaq Fathulloh; Achmad Farid; Muhammad Masyhuri (Institut Agama Islam Syarifuddin Lumajang, 2021)
The objectives of this study are: 1. To determine the influence of leadership on work discipline on Islamic institutions Syarifuddin Wonorejo Lumajang; 2. To find out the influence of Work Discipline Motivation on Islamic Religious Institutions Syarifuddin Wonorejo Lumajang; 3. To determine the effect of Work Discipline on Employee Performance at Syarifuddin Wonorejo Lumajang Islamic Institute; 4. To determine the influence of leadership on employee performance at Syarifuddin Wonorejo Lumajang Islamic Institute; 5. To find out the effect of the Work Discipline Motivation on Syarifuddin Wonorejo Lumajang Islamic Institute. In this study, the authors used quantitative research. The population in this study by census technique is to take all employees at the Syarifuddin Wonorejo Lumajang Islamic Institute, totaling 50 (fifty) employees. By using Structural Equation Modeling Analysis (SEM), the results show that there is a significant influence between Leadership on Work Discipline, There is no significant influence between Motivation on Work Discipline, There is a significant influence between work discipline on employee performance, there is a significant influence between leadership on Employee Performance, there was no significant influence between work motivation and employee performance at the Syarifudin Wonorejo Lumajang Islamic Institute. Keywords: Leadership, Motivation, Discipline, Employee Performance